NILAI AKHLAK BERBASIS KEARIFAN LOKAL - Sunhu Rasik (UIN Fatmawati Sukarno Bengkulu, 2018)
Abstract: The issues raised in this study were 1) How is the form of pepatah petitih Besemah‟s societies in Pagaralam, 2) How is values of attitude of education that meant in pepatah-petitih Besemah societies in Pagaralam. The purpose of this study was to know values of attitude of education that meant ini pepatah-petitih Besemah‟s societies in Pagaralam. This study is qualitative research by using method and for descriftive. Colleting for the data in this sudy was interview and document study. The result of study showed that: (1) Pepatah petitih Besemah Society can be classified into three types. Those are pepatah petitih in form of prohibition, expression or idiom and life principle. (2) The moral eduaciton values that contained in “pepatah petitih” Besemah society were moral of self. and moral of fellow human being. The moral education value of self covered value of obedience, value of hard working, value of responsibility, value of habituation and discipline, value of keeping promises, humble, patient, and honest. The moral education values of human beings were the value of tolerance, the value of affection toward others, the value of justice, the value of sacrifice, and social care.